Tuning nature and temperature of structural and magnetic phase transitions of Mn3Cu1−yMyN1−xCx (M=Ag, Ni) - Born, N-O; Caron, Luana; Seeler, E.; Felser, Claudia (Journal of Alloys and Compounds, 2019)
Antiperovskite materials based on Mn3CuN with Cu partially replaced by Ag or Ni and simultaneous substitution of N by C were synthesized and their magneto-structural transition was studied. By replacing Cu partially with Ag or Ni, Curie temperatures increase, the magnetostructural transition becomes isosymmetric and presents a more second order character. Simultaneous replacement of N by C reverses this trend as the Curie temperature decreases with increasing Ag/Ni content while the structural transition remains non-isosymmetric. Additionally, moderate magnetocaloric effects with magnetic entropy changes around 6 J/Kkg in the range of 130–150 K at a 2 T field change are observed. Finally, the influence of the change in number of valence electrons and cell size by substitution on the transition is discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Antiperovskite; Magnetically ordered materials; Magnetocaloric; Mn; Phase transitions